2000
DOI: 10.1080/016128400248167
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Theory and Adjustment Difficulties in Siblings of Children With Cancer

Abstract: The demands of the childhood cancer experience on children and their parents has been investigated for a number of years. Despite this research, very little emphasis has been placed on well siblings. In the health care profession today, there is a growing perception that the psychosocial needs of the healthy siblings of children with cancer are less sufficiently met than those of other members of the family system. Previous research proposes that well siblings are especially susceptible to a number of adjustme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
0
28
0
5
Order By: Relevance
“…Several studies have identified maladaptive levels of anxiety and depression in healthy siblings of childhood cancer patients [Cain et al, 1964;Spinetta, 1981], although the distress tends to remit once the cancer treatment stops [Van Dongen-Melman et al, 1995]. One possible explanation is that overwhelmed parents may neglect the psychological and physical needs of their healthy children [Sahler et al, 1994;Zeltzer et al, 1996;Houtzager et al, 1999;Murray, 2000] and, perhaps, leave them to contend with feelings of loneliness, fear, anger, hate and jealousy [Martinson et al, 1990;Murray, 1998]. In this way, parent-child bonding or attachment may be harmed and lead to psychological distress in the child [Fanos, 1997;Murray, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified maladaptive levels of anxiety and depression in healthy siblings of childhood cancer patients [Cain et al, 1964;Spinetta, 1981], although the distress tends to remit once the cancer treatment stops [Van Dongen-Melman et al, 1995]. One possible explanation is that overwhelmed parents may neglect the psychological and physical needs of their healthy children [Sahler et al, 1994;Zeltzer et al, 1996;Houtzager et al, 1999;Murray, 2000] and, perhaps, leave them to contend with feelings of loneliness, fear, anger, hate and jealousy [Martinson et al, 1990;Murray, 1998]. In this way, parent-child bonding or attachment may be harmed and lead to psychological distress in the child [Fanos, 1997;Murray, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…Propondo compreender os efeitos da experiência do câncer infantil para os irmãos saudáveis, foi elaborado um estudo (9) utilizando-se como ferramenta conceitual a teoria do apego. O estudo busca explicar a natureza das relações entre as crianças com seus pais, em termos de funções biológicas, e avaliar possíveis distúrbios de comportamento em resposta a prolongada separação com figuras significativas.…”
Section: Impacto Da Doença Nos Irmãos Saudáveisunclassified
“…In studies conducted with siblings of disabled chidren in recent years, it has been found that children with a disabled sibling are also more stressful (8). Siblings of disabled children had psychopathological problems such as stressful life, adaptation problems, increase in the feeling of inadequacy and internal and external behavioral problems and unrealistic responsibilities at home (9,10).…”
Section: Introductionmentioning
confidence: 99%